Local Information in Foreign Exchange Markets - Lukas Menkhoff; Maik Schmeling (Universität Hannover, Wirtschaftswissenschaftliche Fakultät, 2006)
This study shows that order flow in a foreign exchange market only has permanent price impact if it comes from certain regions. These regions are – as predicted by the local information hypothesis – centers of political and financial decision making. It is revealing that orders from other regions only show a very short-lived but no permanent price impact. Local information is so important that it carries over from the usually considered market orders to aggressively-priced limit orders too. The finding is robust to various market conditions, common news shocks and consideration of feedback trading.
Keywords: D82; F31; 330; Local information hypothesis; price impact; limit orders; informed traders